The occurring of Oenothera species in Scandinavia - Rostański, Krzysztof (Biodiversity: Research and Conservation, 2006)
This paper presents results of a taxonomic revision of the specimens of Oenothera L. stored in the major herbaria of Denmark, Norway, Sweden and Finland. The examination of about 3000 specimens revealed that in Scandinavia a total of 45 Oenothera species were collected, and 22 of them were cultivated in gardens (especially in botanical gardens) but the remaining 23 were growing wild. The list of Oenothera species found in Scandinavia is compared with similar lists from the Baltic countries (Estonia, Latvia and Lithuania) and with the list of all Oenothera species identified by me all over Europe (99 species).